2015
DOI: 10.1007/s11269-015-1039-2
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Groundwater-Quality Time-Series Using Self-organizing Maps and Sammon’s Mapping

Abstract: Groundwater extracted from alluvial aquifers close to rivers is vulnerable to contamination by infiltrating river water. Infiltration is often increased during high discharge events, when the levels of waterborne pathogens are also increased. Water suppliers with low-level treatment thus rely on alternative measures derived from information on system state to manage the resource and maintain drinking-water quality. In this study, a combination of Self-Organizing Maps and Sammon's Mapping (SOM-SM) was used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Furthermore, it allows for efficient tailor-made measures to hedge against the risk of breakthroughs in biological filters61 or to avoid the input of peak loads into the distribution system (which can be much easier and/or cheaper than trying to decrease average loads). Moreover, relevant proxy variables (e.g., turbidity, electrical conductivity, pH, SAC 254 ) may be found that are easier/cheaper to measure than TCC, and which correlate sufficiently with bacterial concentrations3664.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it allows for efficient tailor-made measures to hedge against the risk of breakthroughs in biological filters61 or to avoid the input of peak loads into the distribution system (which can be much easier and/or cheaper than trying to decrease average loads). Moreover, relevant proxy variables (e.g., turbidity, electrical conductivity, pH, SAC 254 ) may be found that are easier/cheaper to measure than TCC, and which correlate sufficiently with bacterial concentrations3664.…”
Section: Discussionmentioning
confidence: 99%